Когда атакуют фурии: [роман] / Сергей Самаров - Самаров Сергей Васильевич (Спецназ ГРУ, 2021)
Экземпляры: Селтинская районная библиотека (аб) (20210429) / Инвентарный номер: 207767 / Цена: / Авт.знак: С 17 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6